Communication in a changing world - Dobkin, Bethami A. (McGraw-Hill, 2003)
An exciting new text for the basic hybrid course, Communication in A Changing World is distinguished by its emphasis on ethics and civility in communication; its original, comprehensive and integrated treatment of computer-mediated communication; and, its authentic, engaging examples drawn frequently from popular culture. Communication in A Changing World regards communication as integral to the development of students as responsible citizens in a diverse world. Its goal is to help create good communicators who are skilled in their construction, presentation, understanding and evaluation of messages, and who also have the knowledge and willingness to take responsibility for their communication behaviors.